Factors Affecting Online Buyer’s Loyalty On P2P Cotton page - Khamlidong, Tayakorn (Journal of Management Science Nakhonratchasima University, 2024)
The research was objected to study 1) the demographic factors that affected the loyalty of the online buyers of the traditional shirts on the P2P Cotton page 2) to study the relationship between the marketing mix factors and the loyalty of the buyers of the traditional shirts. online on the P2P Cotton page 3) to study the relationship between the quality of Facebook and the loyalty of the online buyers of local shirts on the P2P Cotton page. It was a quantitative research. The tool for collecting the data was the online questionnaire. The sample group was included with 220 customers, who purchased the products from P2P Cotton. Purposive sampling method was used. The data was analyzed by using the descriptive and inferential statistics; Multiple Regression Analysis. The results of the research revealed that: 1) different occupational demographic factors affected the loyalty of the online buyers of traditional shirts on the P2P Cotton page, and different factors of age, gender, income, status, and education did not affect the loyalty of the online buyers of traditional shirts on the P2P Cotton page 2) the marketing mix factors (6Ps); the product , the price , the distribution channel, the marketing promotion, the personal services and the privacy protection ,affected the loyalty of the online buyers of local shirts on the P2P Cotton page and 3) Facebook quality factors ; the data quality, the system quality, the service quality and the ease of use, affected the loyalty of the online buyers of traditional shirts on the P2P Cotton page, with the statistical significance at the level of 0.05.